Efficiency of HIV services in Nigeria: Determinants of unit cost variation of HIV counseling and testing and prevention of mother-to-child transmission interventions. - Sergio Bautista-Arredondo; Gina La Hera-Fuentes; David Contreras-Loya; Ada Kwan; S Janae Van Buren; Ogbonna O Amanze; Akinyemi Atobatele; Adedayo Adeyemi; Emmanuel Abatta; Kayode M Ogungbemi; Sandra G Sosa-Rubí (PLoS ONE, 2018)
BACKGROUND:Like most countries with a substantial HIV burden, Nigeria continues to face challenges in reaching coverage targets of HIV services. A fundamental problem is stagnated funding in recent years. Improving efficiency is therefore paramount to effectively scale-up HIV services. In this study, we estimated the facility-level average costs (or unit costs) of HIV Counseling and Testing (HCT) and Prevention of Mother-to-Child Transmission (PMTCT) services and characterized determinants of unit cost variation. We investigated the role of service delivery modalities and the link between facility-level management practices and unit cost variability along both services' cascades. METHODS:We conducted a cross-sectional, observational, micro-costing study in Nigeria between December 2014 and May 2015 in 141 HCT, and 137 PMTCT facilities, respectively. We retrospectively collected relevant input quantities (personnel, supplies, utilities, capital, and training), input prices, and output data for the year 2013. Staff costs were adjusted using time-motion methods. We estimated the facility-level average cost per service along the HCT and PMTCT service cascades and analyzed their composition and variability. Through linear regressions analysis, we identified aspects of service delivery and management practices associated with unit costs variations. RESULTS:The weighted average cost per HIV-positive client diagnosed through HCT services was US$130. The weighted average cost per HIV-positive woman on prophylaxis in PMTCT services was US$858. These weighted values are estimates of nationally representative unit costs in Nigeria. For HCT, the facility-level unit costs per client tested and per HIV-positive client diagnosed were US$30 and US$1,364, respectively; and the median unit costs were US$17 and US$245 respectively. For PMTCT, the facility-level unit costs per woman tested, per HIV-positive woman diagnosed, and per HIV-positive woman on prophylaxis were US$46, US$2,932, and US$3,647, respectively, and the median unit costs were US$24, US$1,013 and US$1,448, respectively. Variability in costs across facilities was principally explained by the number of patients, integration of HIV services, task shifting, and the level of care. DISCUSSION:Our findings demonstrate variability in unit costs across facilities. We found evidence consistent with economies of scale and scope, and efficiency gains in facilities implementing task-shifting. Our results could inform program design by suggesting ways to improve resource allocation and efficiently scale-up the HIV response in Nigeria. Some of our findings might also be relevant for other settings.